Changes in sorghum production, soil P forms and P use efficiency following long-term application of manure, compost and straw in a Ferric Lixisol - Dohan Mariam Soma; Delwendé Innocent Kiba; Nana Ewusi-Mensah; Zacharia Gnankambary; François Lompo; Michel Papoaba Sedogo; Robert Clement Abaidoo (Acta Agriculturae Scandinavica. Section B, Soil and Plant Science, 2018)
Low phosphorus availability in cultivated soils limits sustainable crop production in sub‐Saharan Africa. This study aimed at evaluating the effect of long‐term application of different types of organic amendments on soil P forms, P use efficiency and sorghum yields. A long term experiment established in 1980 at Saria in Burkina Faso, comparing the effects of manure, compost and sorghum straw was used. Manure and compost significantly increased organic P and resin‐P by about 35% and 64%, respectively after 10 and 32 years of sorghum cultivation, and HCl‐P after 32 years of cultivation compared to the control. Manure significantly increased NaHCO3-Pi and NaOH-Pi by 63% and 26%, respectively compared to the control. Sorghum straw had little effect on measured soil P forms. Manure and compost were the best in increasing sorghum grain yield, which effect were strongly correlated to soil pH, carbon and nitrogen. The partial factors productivities of P resulting from the application of studied organic amendments were similar and low, but significantly higher than that of the control treatment. Organic amendments with high P content, maintaining soil carbon and pH could be used to improve soil P availability, sorghum yield and reduce the demand for mineral phosphorus fertilizers.